The Effect of Using Video in Teaching Listening at Smp Muhammadiyah 4 Gempol - Uswatun Khasanah (Proceedings of The ICECRS, 2021)
The objective of this research is to find out whether there is any significant difference of students in Listening skill between before and after being taught by using the Video. The research is conducted at SMP Muhammadiyah 4 Gempol Pasuruan. Sample of this study is students in 7th grade class A. The method that is used in this research is quantitative method with pre-experimental design Pretest and postest. To get the data, the researcher gave pre-test, treatment and post-test to the students. The researcher using Video in Teaching Listening. Based on the result of this research, the shows that ,there is significant difference of students test in Teaching Listening class before and after students are given video in litening class. The data obtained are then analyzed using the t-test and obtained with a significant level of 5%, it is known that tcount = 16.56 is greater than t table = 2.06. Thus, it shows that H0 is rejected and Ha is accepted and by using the Eta Squared formula. The results of the calculation obtained a value of 0.91.